Exploring the needs for ESP learning of the learners of Can Tho police college –Towards a suggested ESP syllabus : - Nguyễn, Thị Thu Hiền (Đại học Cần Thơ, 2011)
This research aims at exploring the needs of English for Specific Purpose (ESP) to police students at Can Tho Police College. The research is a survey following the descriptive approach design. The participants attitudes towards the needs of ESP were examined by questionnaires, structured interview and opened interview